Analysis of the Mutational Landscape for Head and Neck Squamous Cell Carcinoma in Africans (African Journal of Biomedical Research, 2023)
Reports suggest that there may be differences in the genetic causes of cancer based on ethnic variations in mutations. However, there is a lack of research on the mutational landscape of head and neck squamous cell carcinoma (HNSCC) in African populations to determine if there are any differences among African patients. This study aims to analyze the mutational landscape of HNSCC in Africans by reviewing available data and identifying any unique mutational patterns or distinctions compared to Caucasian data. The search methodology was based on the PRISMA guidelines checklist. MeSH terms and keywords were used and the Cancer Genome Atlas (TCGA) portal was used to analyze data related to the study objective. The TCGA study evaluated 48 African HNSCC samples. The PIK3CA hotspot mutations E545K, E542K and H1047R recorded the highest mutation implicated in Caucasian cohort but were almost non-existence in the African cohort. Equally relevant were the CDKN2A and TP53 mutations recorded amongst the Caucasian cohort were not detected in the African cohort, rather the African cohort recorded no R80* and one R85* - CDKN2A mutations and none of  the TP53 mutations seen in Caucasian.  In conclusion, studies on HNSCC candidate genes needs to be undertaken in Africa with more of these studies in Sub-Saharan Africa.